![SearchIcon](https://vmkt.vedantu.com/vmkt/PROD/png/bdcdbbd8-08a7-4688-98e6-4aa54e5e0800-1733305962725-4102606384256179.png)
Prove by the vector method ,the law of sine in trigonometry:
$\dfrac{{\sin A}}{a} = \dfrac{{\sin B}}{b} = \dfrac{{\sin C}}{c}$
![seo images](https://www.vedantu.com/question-sets/0c793df9-33c0-470f-829d-79a16846dbc27461902917698361016.png)
Answer
481.2k+ views
Hint: For solving this question we will assume that \[AB = \overrightarrow c ,BC = \overrightarrow a ,AC = \overrightarrow b \] and use the following known information:
For a triangle ABC ,
\[\overrightarrow {AB} + \overrightarrow {BC} + \overrightarrow {CA} = 0\],
Then just solve the question by using the cross product/ vector product of vectors method to get the desired answer.
The magnitude of cross product of two vectors is equal to the product of magnitude of both the vectors and the sine of angle between them.
\[\left| {\overrightarrow x \times \overrightarrow y } \right| = \left| {\overrightarrow x } \right|.\left| {\overrightarrow y } \right|.\sin \theta \]
Where \[\theta \] is the angle between vectors x and y
Complete step-by-step answer:
Let us assume \[AB = \overrightarrow c ,BC = \overrightarrow a ,AC = \overrightarrow b \]
Now as we know that for a triangle
\[\overrightarrow {AB} + \overrightarrow {BC} + \overrightarrow {CA} = 0\]
Since we know that:
\[\overrightarrow {CA} = - \overrightarrow {AC} \]
Hence putting the value we get:-
\[\overrightarrow {CA} = - \overrightarrow b \]
Hence putting the respective values we get:-
\[\vec a - \vec b + \vec c = 0\]
Using cross product of vectors method, multiply by $\vec a$ both side
\[\vec a \times (\vec a - \vec b + \vec c) = a \times \vec 0\]
Now as we know that:
\[\overrightarrow x \times \left( {\overrightarrow y + \overrightarrow z } \right) = \overrightarrow x \times \overrightarrow y + \overrightarrow x \times \overrightarrow z \]
Applying this formula we get:-
\[(\overset{\lower0.5em\hbox{$\smash{\scriptscriptstyle\leftarrow}$}}{a} \times \vec a) - (\vec a \times \vec b) + (\vec a \times \vec c) = \vec 0\]
We know that the cross product of same vectors is zero
Therefore,
\[(\vec a \times \vec a) = 0\]
Putting this value we get:-
\[
0 - (\vec a \times \vec b) + (\vec a \times \vec c) = \vec 0 \\
(\vec a \times \vec b) = (\vec a \times \vec c) \\
\]
Now as we know that the magnitude of cross product of two vectors is equal to the product of magnitude of both the vectors and the sine of angle between them.
\[\left| {\overrightarrow x \times \overrightarrow y } \right| = \left| {\overrightarrow x } \right|.\left| {\overrightarrow y } \right|.\sin \theta \]
Where \[\theta \] is the angle between vectors x and y.
Hence applying this formula for both LHS and RHS we get:-
Since it is given that the angle between vectors a and b is \[\pi - C\] and angle between the vectors a and c is \[\pi - B\]
Therefore substituting the values in above formula we get:-
\[
\left| a \right|\left| b \right|\sin (\pi - C) = \left| c \right|\left| a \right|\sin (\pi - B) \\
\Rightarrow ab\sin (\pi - C) = ca\sin (\pi - B) \\
\]
Now since we know that
\[\sin (\pi - \theta ) = \sin \theta \]
Hence we get:-
$b\sin C = c\sin B$
\[ \Rightarrow \dfrac{{\sin C}}{c} = \dfrac{{\sin B}}{b}\]……………….(1)
Similarly, we can prove that
$\dfrac{{\sin A}}{a} = \dfrac{{\sin B}}{b}$………………..(2)
Hence from equations 1 and 2 we get:-
$\dfrac{{\sin A}}{a} = \dfrac{{\sin B}}{b} = \dfrac{{\sin C}}{c}$
Hence proved
$\dfrac{{\sin A}}{a} = \dfrac{{\sin B}}{b} = \dfrac{{\sin C}}{c}$
Note: In this type of question students should first analyse the diagram instead of solving the equations. All the vectors should be taken according to their directions.
Also while calculating the magnitude of the vector product, students should take the correct angle between the two vectors.
For a triangle ABC ,
\[\overrightarrow {AB} + \overrightarrow {BC} + \overrightarrow {CA} = 0\],
Then just solve the question by using the cross product/ vector product of vectors method to get the desired answer.
The magnitude of cross product of two vectors is equal to the product of magnitude of both the vectors and the sine of angle between them.
\[\left| {\overrightarrow x \times \overrightarrow y } \right| = \left| {\overrightarrow x } \right|.\left| {\overrightarrow y } \right|.\sin \theta \]
Where \[\theta \] is the angle between vectors x and y
Complete step-by-step answer:
Let us assume \[AB = \overrightarrow c ,BC = \overrightarrow a ,AC = \overrightarrow b \]
Now as we know that for a triangle
\[\overrightarrow {AB} + \overrightarrow {BC} + \overrightarrow {CA} = 0\]
Since we know that:
\[\overrightarrow {CA} = - \overrightarrow {AC} \]
Hence putting the value we get:-
\[\overrightarrow {CA} = - \overrightarrow b \]
Hence putting the respective values we get:-
\[\vec a - \vec b + \vec c = 0\]
Using cross product of vectors method, multiply by $\vec a$ both side
\[\vec a \times (\vec a - \vec b + \vec c) = a \times \vec 0\]
Now as we know that:
\[\overrightarrow x \times \left( {\overrightarrow y + \overrightarrow z } \right) = \overrightarrow x \times \overrightarrow y + \overrightarrow x \times \overrightarrow z \]
Applying this formula we get:-
\[(\overset{\lower0.5em\hbox{$\smash{\scriptscriptstyle\leftarrow}$}}{a} \times \vec a) - (\vec a \times \vec b) + (\vec a \times \vec c) = \vec 0\]
We know that the cross product of same vectors is zero
Therefore,
\[(\vec a \times \vec a) = 0\]
Putting this value we get:-
\[
0 - (\vec a \times \vec b) + (\vec a \times \vec c) = \vec 0 \\
(\vec a \times \vec b) = (\vec a \times \vec c) \\
\]
Now as we know that the magnitude of cross product of two vectors is equal to the product of magnitude of both the vectors and the sine of angle between them.
\[\left| {\overrightarrow x \times \overrightarrow y } \right| = \left| {\overrightarrow x } \right|.\left| {\overrightarrow y } \right|.\sin \theta \]
Where \[\theta \] is the angle between vectors x and y.
Hence applying this formula for both LHS and RHS we get:-
Since it is given that the angle between vectors a and b is \[\pi - C\] and angle between the vectors a and c is \[\pi - B\]
Therefore substituting the values in above formula we get:-
\[
\left| a \right|\left| b \right|\sin (\pi - C) = \left| c \right|\left| a \right|\sin (\pi - B) \\
\Rightarrow ab\sin (\pi - C) = ca\sin (\pi - B) \\
\]
Now since we know that
\[\sin (\pi - \theta ) = \sin \theta \]
Hence we get:-
$b\sin C = c\sin B$
\[ \Rightarrow \dfrac{{\sin C}}{c} = \dfrac{{\sin B}}{b}\]……………….(1)
Similarly, we can prove that
$\dfrac{{\sin A}}{a} = \dfrac{{\sin B}}{b}$………………..(2)
Hence from equations 1 and 2 we get:-
$\dfrac{{\sin A}}{a} = \dfrac{{\sin B}}{b} = \dfrac{{\sin C}}{c}$
Hence proved
$\dfrac{{\sin A}}{a} = \dfrac{{\sin B}}{b} = \dfrac{{\sin C}}{c}$
Note: In this type of question students should first analyse the diagram instead of solving the equations. All the vectors should be taken according to their directions.
Also while calculating the magnitude of the vector product, students should take the correct angle between the two vectors.
Recently Updated Pages
Master Class 11 Accountancy: Engaging Questions & Answers for Success
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Express the following as a fraction and simplify a class 7 maths CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
The length and width of a rectangle are in ratio of class 7 maths CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
The ratio of the income to the expenditure of a family class 7 maths CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
How do you write 025 million in scientific notatio class 7 maths CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
How do you convert 295 meters per second to kilometers class 7 maths CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Trending doubts
10 examples of friction in our daily life
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Difference Between Prokaryotic Cells and Eukaryotic Cells
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
State and prove Bernoullis theorem class 11 physics CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
What organs are located on the left side of your body class 11 biology CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Write down 5 differences between Ntype and Ptype s class 11 physics CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)